Evaluation of Carbonate Reservoir Based on Electrical Imaging Floating Scale Porosity Spectrum - LIU Zhang; SUN Jianmeng; HE Juan; CHENG Xiaobo; DONG Huaimin; CHI Peng (Cejing jishu)
The Mishrif formation in the X oilfield of Iraq is a thick layer of reef beach carbonate rock, which is influenced by multiple factors such as sedimentation, diagenesis, and tectonic processes. The pore structure of the reservoir is complex and highly heterogeneous, resulting in significant differences in vertical physical properties of the reservoir. However, conventional logging data and nuclear magnetic resonance logging data have shown that there is little difference in reservoir porosity in the study area. Therefore, it is difficult to construct a reservoir classification method based solely on the above data to characterize the differences between reservoir pore structures and the relationship between porosity and permeability. Firstly, the absolute and floating scale porosity spectra are constructed based on the electrical imaging logging data, and the characteristic parameters are extracted to divide the pore structure into five types. Then, based on conventional logging data and core well physical property data, the pore structure types divided by electrical imaging porosity spectrum are used to scale the conventional logging data into five reservoir types. Finally, porosity and permeability models are constructed for different reservoir types, and the correlation between these two physical parameters is good. Combined with the characteristics of core, cast thin section, and multistage centrifugal nuclear magnetic resonance experimental data, it’s found that the pore structure, porosity and permeability characteristics of different reservoir types are significantly different, which fully reflected the characteristics of carbonate reservoir with strong heterogeneity caused by diagenesis. This reservoir evaluation method is of great significance for accurate classification of reservoirs and improving the accuracy of reservoir physical property evaluation.